2017
DOI: 10.1038/srep44508
|View full text |Cite
|
Sign up to set email alerts
|

Reduced graphene oxide composites with water soluble copolymers having tailored lower critical solution temperatures and unique tube-like structure

Abstract: Nanohybrids of graphene with water soluble polymer were synthesized using ‘grafting from’ method. GO, prepared by modified Hummers’ method, was first reacted with sodium azide. Alkyne-terminated RAFT-CTA was synthesized by reaction of propargyl alcohol and S-1-dodecyl-S’-(α,α‘-dimethyl-α”-acetic acid) trithiocarbonate. RAFT-CTA was grafted onto the GO sheets by facile click-reaction and subsequently, N-isopropylacrylamide (NIPAM) and N-ethyleacrylamide (NEAM) were polymerized on graphene sheets via RAFT polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 50 publications
1
4
0
2
Order By: Relevance
“…A steady increase in this ratio is observed with increasing FD, from about 1 for GO ( Table 4 , entry 1) to 1.75 for the derivative with the highest FD ( Table 4 , entry 7), which demonstrates a decrease in the structural order, that is, in the size of the in-plane sp 2 domains, owed to the covalent grafting of the HDI chains onto the GO surface. An analogous trend of I D /I G increase has been reported upon covalent functionalization of GO with other organic molecules such as 4-aminobenzenesulfonic acid [ 52 ] or polymers like poly(N-isopropylacrylamide) (PNIPAM) [ 53 ], hinting that the functionalization process results in graphitic domains that are smaller than those of GO.…”
Section: Resultssupporting
confidence: 58%
“…A steady increase in this ratio is observed with increasing FD, from about 1 for GO ( Table 4 , entry 1) to 1.75 for the derivative with the highest FD ( Table 4 , entry 7), which demonstrates a decrease in the structural order, that is, in the size of the in-plane sp 2 domains, owed to the covalent grafting of the HDI chains onto the GO surface. An analogous trend of I D /I G increase has been reported upon covalent functionalization of GO with other organic molecules such as 4-aminobenzenesulfonic acid [ 52 ] or polymers like poly(N-isopropylacrylamide) (PNIPAM) [ 53 ], hinting that the functionalization process results in graphitic domains that are smaller than those of GO.…”
Section: Resultssupporting
confidence: 58%
“…The size of the side group, which matched the hexagonal ordering of the molecular chains, and the other amorphous halo peak at 19.7° were attributed to the van der Waals distance. HRGO/PS (0.1%) showed similar XRD peaks to PS, while the XRD peaks of 1% and 2% HRGO/PS became narrower and more intense, indicating some kind of crystalline structure formation [20]. Mainly, it could be attributed to a relatively intense number of staked graphene layers with the increase in HRGO content.…”
Section: Resultsmentioning
confidence: 99%
“…Since the introduction of click chemistry, it has met the need of researchers in different elds of science for a set of powerful, highly reliable, and selective reactions for the rapid synthesis of useful new compounds and combinatorial libraries. 9 Click reactions, and above all Cu(I)-catalyzed Huisgen cycloaddition of azide and alkyne (CuAAC), have made their way into modication of polymers, 10 nanoparticles, 11 carbon nanomaterials, [12][13][14][15][16] and proteins. 17 GO nanosheets were assembled together through an azide-alkyne click reaction to obtain a highly permeable polypropylene membrane, 18 while Lin et al used an azoaromatic crosslinker to connect alkyne-containing GO sheets.…”
Section: Introductionmentioning
confidence: 99%
“…19 In our recent study, we reported water soluble copolymers having tailored lower critical solution temperatures and a unique tube-like structure, in which a reversible additionfragmentation transfer agent was attached to GO sheets via click chemistry. 14 Polyoligomeric silsesquioxanes (POSS) have a unique cagelike structure with eight organic functionalities, which make it suitable as a core or crosslinking molecule since it is soluble in a wide range of organic solvents. POSS has been used to modify polymers, 20 carbon nanotubes, 21 and nanoparticles.…”
Section: Introductionmentioning
confidence: 99%